Instructional Design of Engineering Courses with Online Certifications - Reflections and Experiences - Chandrasekaran, Jeyamala; S, Thiruchadai Pandeeswari; S, Pudumalar (Journal of Engineering Education Transformations, 2025)
Owing to the exploding growth of Internet technologies and IT infrastructure, education from primary to university level has taken a new dimension in online platforms. In Engineering Education perspective, Online educational platforms provide anytime, anywhere access to quality technical content to everyone in the world. Renowned universities and academies have joined hands with MOOC service providers and offer universally recognized certification courses. These online certification courses can be considered as a powerful tool for empowering learners with new-age technical skills and knowledge. This article explores the possibilities of including online certifications in regular academic courses, thereby leveraging them to evolve an effective Instructional Design. A systematic method to include online courses and their corresponding certifications as a part of the assessment in institute-level courses has been developed. The experimental study has been investigated on a sample of three undergraduate engineering courses namely Cloud Computing, Blockchain Technologies and Data Analytics offered for the B.Tech Information Technology undergraduate course. Around 180 learners and three instructors participated in the research study. The proposed instructional design has resulted in a significant enhancement in the learning outcomes and student satisfaction index. Various plans to address the implementation challenges in integrating online certifications are also discussed. The authors believe that the manuscript will guide the faculty interested in utilizing online resources for classroom teaching.